Fatigue action on crane runway beams. (June 2021) - Euler, Mathias; Taylor, Colin
Abstract: The supporting structure of an overhead traveling crane is subject to cyclic loading. The crane runway beams are parts of this structure traveled over by the crane during each crane passage. Therefore, their fatigue resistance has to be verified according to structural Eurocode 3 in more than 30 countries that are members of European Committee for Standardization (CEN) and potentially more than 50 countriesaround the world. For the verification, the expected fatigue loading during the design service life has to be estimated. A new proposal is presented how to predict the fatigue loading of the crane runway beams based on the type of crane operation. Graphical abstract: Unlabelled Image Highlights: Monte Carlo simulation of random wheel load spectra for crane runway beams. Crane self-weight significantly affects the fatigue action of crane runway beams. Exact information on working position history of crane's trolley matters. Findings allow for a more precise description of fatigue action for crane runways. User-friendly tool to classify crane runway beams based on crane type.